PENGARUH KOMUNIKASI, KEDISIPLINAN, DAN TANGGUNG JAWAB TERHADAP KINERJA PEGAWAI DI UPT DINAS PENDIDIKAN POLOKARTO SUKOHARJO - -, Suwardi -; Wahyudi, Amin - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2010)
Â  ABSTRACT Unit of District Education Office Polokarto Sukoharjo is a government organization that aims to implement educational services for the community. To achieve that purpose, support the good performance of all employees. The number of samples taken 40 people in full of the entire employee population UPT District Education Office Polokarto Sukoharjo. Data were collected through questionnaires, then analyzed by Multiple Linear Regression, F-test and t-test. The studies results are: (1) communication has a positive and significant impact on Employee Performance Unit District Education Office Polokarto Sukoharjo, (2) discipline does not have a positive and significant impact on Employee Performance (3) has no responsibility for a positive and significant impact on Employee Performance Unit District Education Office Polokarto Sukoharjo, (4) Approximately 14% of variation in the dependent variable (performance) can be explained by variations in the set of independent variables (communication, discipline, and responsibility). Keywords: communications, discipline, responsibility, performance